OTORITAS KEPEMIMPINAN SEORANG AYAH TERHADAP ANAK: REFLEKSI KISAH NABI IBRAHIM DALAM PENGASUHAN AKTIF PADA KELUARGA - Abdul Hadinoto; Diyanah Hanifiyah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
Child rearing in the modern era faces complex challenges, ranging from moral crises to the phenomenon of fatherlessness, which triggers the degradation of the younger generation's character. This qualitative research through literature study aims to explore the concept of fatherhood as qawwam (head of the household) by reflecting on the story of Prophet Ibrahim AS. The results show that effective fatherhood is not autocratic and based on coercion, but rather democratic and religious exemplary leadership. Prophet Ibrahim's approach in facing severe trials—such as interactive dialogue with Prophet Ismail—offers a parenting model based on empathy, open communication, and spiritual resilience. This study concludes that strengthening fatherly authority through re-spiritualization, collaboration with mothers, and active psychological presence is crucial for building children's resilience to the challenges of the times and ensuring a future generation with integrity.